29th Digital Avionics Systems Conference 2010
DOI: 10.1109/dasc.2010.5655506
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flight management system predictions of idle-thrust descents

Abstract: To enable arriving aircraft to fly optimized descents computed by the flight management system (FMS) in congested airspace, ground automation must accurately predict descent trajectories. To support development of the predictor and its uncertainty models, descents from cruise to the meter fix were executed using vertical navigation in a B737-700 simulator and a B777-200 simulator, both with commercial FMSs. For both aircraft types, the FMS computed the intended descent path for a specified speed profile assumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The other major source of this error is likely error in the descent wind forecast used by the FMS, which Bronsvoort et al [7] investigated. Stell [8] test bench simulator, which could increase prediction error. Further research is needed to see whether ground predictors might be able to reduce these errors.…”
Section: Discussionmentioning
confidence: 99%
“…The other major source of this error is likely error in the descent wind forecast used by the FMS, which Bronsvoort et al [7] investigated. Stell [8] test bench simulator, which could increase prediction error. Further research is needed to see whether ground predictors might be able to reduce these errors.…”
Section: Discussionmentioning
confidence: 99%
“…26 The Global 5000 analysis results suggested that fixed-FPA decents were much more predictable than idle-thrust descents typically performed by large commercial jets, of which the ground predictions had top-of-descent errors around 5 to 10 nmi. 18,27 While a simple, fixed-FPA descent procedure using prescribed clearances was introduced for the purposes of the flight tests, EDA itself lacks a defined descent procedure and corresponding algorithm for small jets. This hampers EDA's capability to deliver small jet arrivals to the metering fix on time and impacts EDA's ability to maintain separation involving the arrival aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…Reynolds, Ren and Clarke (6) concluded after different tests in the Nottingham East Midlands Airport that CDA effectively reduced fuel burn and noise near the terminals simply by keeping the aircraft at the higher altitude possible before creating the descent. Stell (7) used an efficient descent advisor, which is a method to predict the latest descent point (equivalent to the TOD) in order to apply the 3D PAM technique, but it still needs an improved ATC in order to operate at its maximal efficiency.…”
Section: Introductionmentioning
confidence: 99%